EUBORDERSCAPES Bordering Political Landscapes and Social Arenas Potentials and Challenges of Evolving Border Concepts in a Post Cold War World - (:unkn) unknown (My University, 2025)
In order to gauge its significance, conceptual change in the study of borders must be seen in relation to fundamental social, economic and geopolitical transformations that have taken place in the past decades. In addition, major paradigmatic shifts in scientific debate, and in the social sciences in particular, must also be considered. Recognising the close interrelationships between social change and paradigm shifts, the EUBORDERSCAPES project will analyse the evolving concept of borders in terms of a mutually linked emergence of “post-national”, “post-colonial”, “postmodernist” and “post-Communist” strands of inquiry. State borders are the frame of reference, rather than ethnographic/anthropological boundaries. However, this approach emphasises the social significance and subjectivities of state borders while critically interrogating “objective” categories of state territoriality and international relations. The research proposed here will, furthermore, not only be focused at the more general, at times highly abstract, level of conceptual change. This approach will also allow us to compare and contrast how different and often contested conceptualisations of state borders (in terms of their political, social, cultural and symbolic significance) resonate in concrete contexts at the level of everyday life.